Developing a Model for Religious Tolerance Management Among University Students - Rukimin Rukimin; Agus Pahrudin; Koderi Koderi; Ahmad Fauzan (AL-ISHLAH: Jurnal Pendidikan, 2024)
Religious tolerance is a critical aspect of student development, particularly in diverse educational environments. This study focuses on developing a Religious Tolerance Management Model at Baitul Arqom, Muhammadiyah Mataram University (UMMAT), to promote tolerance among students. The research employs the Dick and Carey system design and a Research and Development (RD) approach. The study involves systematic stages, including model design, flowchart creation, and the development of modules as final outputs. The resulting Religious Tolerance Management Model comprises specific objectives, indicators, training goals, learning materials, and instructional methods. Key components include: (1) the basics of religious tolerance, (2) student religious tolerance, (3) multiculturalism in religion, (4) tolerance and pluralism, (5) management model design, (6) implementation strategies, and (7) follow-up mechanisms. The model focuses on fostering tolerance attitudes, emphasizing organizing group behaviors and mobilizing peer engagement. By implementing the proposed model, Baitul Arqom participants demonstrated improved abilities to organize and influence others in fostering religious tolerance. The structured module design facilitates practical learning steps, time allocation, and assessment to ensure effective outcomes. The study successfully develops a Religious Tolerance Management Model that enhances student attitudes toward religious tolerance at UMMAT. This model serves as a valuable framework for promoting harmony and pluralistic understanding in higher education institutions.